Correlation the Distance of the Location Found With the Size and Dominant Index of Eel in East Nusa Tenggara Waters - Lukas, Ade Yulita Hesti; Sine, Kiik Gretty; Salosso, Yuliana; Santoso, Priyo (International Journal of Scientific Research and Management (IJSRM), 2022)
The existence of eels in a freshwater area is influenced by various factors, one of which is the availability of habitats that are suitable for the life of eels. East Nusa Tenggara Province is an archipelago that is mentioned as one of the distribution areas for eel in Indonesia. However, the type and size of eel is strongly influenced by the distance it finds. The farther the river is from the estuary, the larger the size of the eel and the different types. As eurihaline migratory fish, eels can swim far upstream to find a suitable habitat for their life. This study aims to analyze the relationship between location distance and the size and dominance index of eel in freshwater in East Nusa Tenggara (NTT). This research was conducted from October to April. The results obtained are that the three rivers in East Nusa Tenggara province, namely the Tarus river in Kupang district, the Oetona river in Kupang city and the Kamaifui river in Alor district, managed to catch 71 eels at a fishing distance of 0.69 km to 7.86 km. from the mouth of the river. Based on the ano-dorsal analysis, two types of eel caught in the Tarus and Kamaifui rivers were identified, namely Anguilla marmorata and Anguilla nebulosa nebulosa, while in the Oetona river only A. marmorata was found. Based on the calculation of the dominance index, the most dominant species in fresh waters of NTT is A. marmorata.